Highly permeable and ultrastretchable E-textiles with EGaIn-superlyophilicity for on-skin health monitoring, joule heating, and electromagnetic shielding. (April 2023) - Dong, Jiancheng; Tang, Xinwei; Peng, Yidong; Fan, Chonghui; Li, Le; Zhang, Chao; Lai, Feili; He, Guanjie; Ma, Piming; Wang, Zicheng; Wei, Qufu; Yan, Xiu-Ping; et al.
Abstract: The prosperity of wearable and healthcare electronics yearns for the compact integration of multi-functionalities including detectability for various electrophysiological signals, thermal/moisture management, and electromagnetic wave protection. Herein, highly breathable and ultrastretchable styrene-ethylene-butylene-styrene (SEBS)-Ag-liquid metal (SSLM) nonwoven electronic textiles are fabricated as versatile on-skin bioelectrodes for accurate health monitoring, Joule heating, and electromagnetic interface (EMI) shielding. Taking advantage of the reactive alloying between liquid metal and magnetron sputtered silver nanoparticles, ultra-conductive eutectic gallium-indium (EGaIn) is intimately and uniformly encapsulated on superlyophilic SEBS microfibers after activation via monolithic pre-stretching. Benefiting from the highly deformable, extremely stable, and 3D interconnected conducting networks, the nonwoven E-textiles demonstrate exceptional EMI shielding effectiveness (75.3 dB at frequencies of 8.2–12.8 GHz, and still maintain 31.7 dB at 300% elongation), and efficient Joule heating performance also under large-scale deformation (120%). Moreover, the breathable SSLM E-textiles used as skin-attachable bioelectrodes even manifest prominent monitoring performance for biophysical signals (breath, phonation, and joint bending), surface electromyography signals (sEMG), and electroencephalogram signals (EEG). Therefore, the superlyophilicity and superior performance of the liquid metal E-textiles enable a wide range of applications in next-generation skin electronics and protective textiles. Graphical Abstract: ga1 Highlights: The electronic textile has superlyophilicity to liquid metal due to the fast alloying. monolithic stretch activation is used to recover the breathability of liquid metal textile. obtained electronic textile has a high conductivity upon 1000% elongation. the electronic textile shows efficient EMI shielding and Joule heating performance. the electronic textile can monitor human biophysical and bioelectrical signals.